The consequences of the 1989 changes in the socio-political activity of Lemkos in Poland and the United States of America - Tyda, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the communist period, the Lemko community did not have its own separate ethnic organization in Poland. In the USA, the Lemkos were able to conduct social and political activities without any obstacles. Even before World War II, two important organizations were established: the Russophile Lemko-Soyuz and the Ukrainophile Organization for the Defense of Lemkivshchyna in America.
Keywords: Lemko; emigration; diaspora; Poland; United States of America